Metodologia de previsão de recessões: um estudo econométrico com aplicações de modelos de resposta binária - Saúde, Arthur Moreira (2017)
This paper aims to create an econometric model capable of anticipating recessions in the United States economy, one year in advance, using not only monetary market variables that are already used by economists, but also capital market variables. Using a data span from 1959 to 2016, it was observed that the yield spread continues to be an explanatory variable with excellent predictive power over recessions. Evidence has also emerged of new variables that have very high statistical significance, and which offer valuable contributions to the regressions. Out-of-sample tests have been conducted which suggest that past recessions would have been predicted with substantially higher accuracy if the proposed Probit model had been used instead of the most widespread model in the economic literature. This accuracy is evident not only in the predictive quality, but also in the reduction of the number of false positives and false negatives in the regression, and in the robustness of the out-of-sample tests.